Penerapan Sistem E-Faktur dan Kepatuhan Pengusaha Kena Pajak dengan Pemahaman Internet Sebagai Variabel Moderasi - Kusumawati, I Gusti Ayu Putu; Jati, I Ketut (E-Jurnal Akuntansi; Vol 32 No 10 (2022), 2022)
The e-invoice system is an electronic tax invoice application provided by the Directorate General of Taxes that can be accessed via the internet to facilitate taxable entrepreneurs in carrying out their tax obligations. This study aims to determine the effect of the e-invoicing system on the compliance of taxable entrepreneurs with the understanding of the internet as a moderating variable. The research was conducted on taxable entrepreneurs registered at the South Badung Pratama Tax Service Office. The research sample amounted to 60 using the convenience sampling method. The data analysis technique used is Simple Linear Regression Analysis and Moderated Regression Analysis (MRA) Method. The results showed that the e-invoicing system variable had a positive and significant effect on the Compliance of Taxable Entrepreneurs, while the understanding of the internet did not moderate the effect of the Implementation of the E-Invoicing System on the Compliance of Taxable Entrepreneurs. Keywords E-Invoices; Taxable Entrepreneur Compliance; Internet Understanding.